PENGARUH MODEL PROJECT BASED LEARNING METODE MIND MAP TERINTEGRASI NILAI ANTI KORUPSI TERHADAP KEBERANIAN BERPENDAPAT PADA MATA PELAJARAN IPS DI KELAS VIII SMPN 9 BANDUNG - Ahmad Fajrudin, - (2022)
The problem on this research is the low of students's dare to speak up in social studies learning. This research aims to analyze the effect of project based learning model with mind map method integrated with anticoruption value on student's dare of speak up in social studies class. Sample used in this research are students from VIII-J and VIII-I SMPN 9 Bandung at program teaching of 2022. This research use Quasi-experimentation desaign as a research design which students of VIII-J as a experimental group using project based learning model with mind map method integrated with anticoruption value and students of VIII-I as a control group using problem based learning model with small discussion group method. After analyze the data using indpendent sample t test, researcher conclude that there is no effect between project based learning with mind map method integrated with anticoruption value on student's dare of speak up with sig. value of 0,878>0.05. Researcher imply that construtivism theory, which says that learners construct their own knowledge, takes a long time and students need different treatment of their own. Situation and condition in each school are also not always the same, because not all school have facillity that can provide student activities and creativity.